1978
DOI: 10.1016/s0022-5347(17)57526-6
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Papillary Transitional Cell Carcinoma of the Bladder and its Treatment in an Unselected Population on the Basis of Histologic Grading

Abstract: Between 1950 and 1965, 365 patients were treated for transitional cancer of the bladder at our hospitals. A retrospective study was done, using clinical records and a histopathologic review to determine the long-term natural history of this population when treated conservatively. The natural history of 3 separate patient populations was discovered, based solely on the grading of the transurethrally resected fragments. Based on the grade on initial presentation these patients were divided into grades I, II and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
7

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(36 citation statements)
references
References 11 publications
2
25
1
7
Order By: Relevance
“…In this prospective trial, the observation of the control group has confirmed the high recurrence rate of superfi cial bladder tumors, with at least 20% chance of progres sion of the recurrent cancer [18][19][20], This study has also confirmed previous reports indicating that intravesical BCG therapy alters favorably the pattern of tumor recur rence in a significant percentage of patients with superfi cial bladder carcinoma [7][8][9][10][11][12][13][14][15][16][17], Sixty-seven percent of the patients in the BCG group were free of tumor recur rences for a mean follow-up of approximately 29 months, compared to only 42% of the control patients for almost the same follow-up period. Likewise, the mean times to tumor recurrences and the rates of tumor recurrences per 100 patient months were 13.36 versus 9.94 months and 1.69 versus 4.41 recurrences, respec tively (p < 0.05).…”
Section: Discussionmentioning
confidence: 59%
“…In this prospective trial, the observation of the control group has confirmed the high recurrence rate of superfi cial bladder tumors, with at least 20% chance of progres sion of the recurrent cancer [18][19][20], This study has also confirmed previous reports indicating that intravesical BCG therapy alters favorably the pattern of tumor recur rence in a significant percentage of patients with superfi cial bladder carcinoma [7][8][9][10][11][12][13][14][15][16][17], Sixty-seven percent of the patients in the BCG group were free of tumor recur rences for a mean follow-up of approximately 29 months, compared to only 42% of the control patients for almost the same follow-up period. Likewise, the mean times to tumor recurrences and the rates of tumor recurrences per 100 patient months were 13.36 versus 9.94 months and 1.69 versus 4.41 recurrences, respec tively (p < 0.05).…”
Section: Discussionmentioning
confidence: 59%
“…15 Nine patients (5%) died of bladder cancer among 155 patients with Grade 1 urothelial carcinoma. 16 Mufti et al 23 reviewed 198 patients with Grade 1 urothelial carcinoma and found that only 53% of patients remained cancer free at 5 years; the actuarial cancer mortality rate was 4%.…”
Section: Figurementioning
confidence: 99%
“…Three quarters of all cases present as superficial disease and whilst half of these cases are cured by simple treatment, about half will develop recurrences (Gilbert et al, 1978). The field change theory of recurrence proposes that each recurrence has arisen de novo from a generalized precancerous urothelium (Raghavan et al, 1990;Harris and Neal, 1992).…”
mentioning
confidence: 99%